Estrategias didácticas y su incidencia en el desarrollo del pensamiento creativo en los estudiantes de la UE Ricaurte, Urdaneta. 2022 - Muñoz Pérez, Cinthya Nathaly (2023)
The present investigative work was carried out with the purpose that the teachers commit to execute the development of creative thinking in a correct way to the students of the Ricaurte Educational Unit in the same way which allow their students to develop the interdisciplinarity that is so intended. From the Ministry of Education, as a primary objective, the degree of creativity shown by students in the fourth year of basic education was recognized. In this work several investigations were carried out, which were related to didactic strategies, development of creative thinking, and very importantly also about creativity. In order to obtain a feasible result, the surveys and observation sheet were carried out on students, the same ones that resulted during the activities, the teachers observed how important it is to stimulate the creative thinking of a student, in this section the development of thinking will be recognized as important. in different situations, and from this joint problem solving, students are happier when they have more feelings. It should always be appreciated that creativity is shared by all people to a greater or lesser extent and if done right it will encourage the development of creative thinking and if stimulated properly it will encourage the development of creative thinking and allow your imagination to shine. Making a student creative is a student with a great idiosyncrasy, who will benefit throughout his career, this will make him make decisions, as in his relationships with other elements of society.